Analysis of Readiness for Primary Service Integration Using the Hot-Fit Method at the Public Health Center - Muhammad Rohani; Ratna Wardani; Agusta Dian Ellina (Indonesian Journal of Global Health Research, 2025)
Strengthening primary health care services is essential to improve the achievement of minimum health service standards. Primary Care Integration aims to reorganize existing primary health care services, enabling them to serve the entire Indonesian population with comprehensive and quality services by coordinating primary health care services based on the life cycle and no longer on programs. This study aims to explore the readiness of human resources, organization and governance, and technology in health centers to implement PCI. This descriptive study was conducted using a qualitative approach with 15 respondents from various job backgrounds. The research was conducted at Ipuh Bangun Jaya Health Center from August to October 2024. In-depth interview results were processed and validated through field observations, resulting in 18 sub-themes. Sub-themes 1-3 are about understanding PCI; sub-themes 4-8 are about human resource readiness; sub-themes 9-14 are about organizational and governance readiness; and sub-themes 15-18 are about technology readiness. Data analysis involved data reduction, data presentation and conclusion and verification. The research findings show that Human Resources at Ipuh Bangun Jaya Health Center have good efficacy and individual attributes to support the implementation of primary care integration at the Health Center. The organization and governance of Ipuh Bangun Jaya Health Center show the existence of management support as one form of good principal support to move towards the implementation of primary care integration at the Health Center. The information technology available at Ipuh Bangun Jaya Health Center is adequate for the implementation of primary care integration at the Health Center as one of the available principal supports. Although the valence of change is not yet very strong, the efficacy of change and the situation of change have been felt and expressed by employees in their daily activities. Things that need to be improved to encourage change include: widespread socialization to all employees according to clusters, structured socialization of policy products, and adequate internet access. The study concludes that Ipuh Bangun Jaya Health Center has strong human resources, governance, and IT support for primary care integration. However, improvements in socialization and internet access are needed for successful implementation.